Development of a steady state visual evoked potential (SSVEP)-based brain computer interface (BCI) system - Leow, R.S.; Ibrahim, F.; Moghavvemi, M. (2007)
This paper describes the development of a synchronous, online brain computer interface (BCI) system based on detecting the steady-state visual evoked potential (SSVEP). The system includes a programmable visual stimulator, EEG amplifier with filter system, data acquisition card, and signal processing and classification algorithms. Two types of experiments were carried out; training experiments were conducted to determine three optimal frequencies for each and every subject. For the testing experiments, three visual stimuli were presented simultaneously to the subject. Subject was required to focus his/her attention only on one of the target stimulus, and the system will detect the targeted stimulus the subject was focusing on. Five subjects have participated in the study with average detection accuracy of 83.10. Â©2007 IEEE.